Efficacy of erector spine plane block in two different approaches to lumbar spinal fusion surgery: a retrospective pilot study - Birnbaums, Jānis Verners; Ozoliņa, Agnese; Solovjovs, Leonids; Glāzniece-Kagane, Zane; Nemme, Jānis; Logina, Ināra (Frontiers in Medicine, 2024)
Background: Erector spine plane block (ESPB) has been widely used in spinal surgery, although there are variable data about its efficacy. Objectives: To evaluate the efficacy of ESPB in elective lumbar spinal fusion surgery patients with two different surgical approaches. Materials and methods: Retrospectively were included 45 elective lumbar transpedicular fusion (TPF) surgery patients undergoing open surgery with different approaches (posterior transforaminal fusion approach (TLIF) or combined posterior and anterior approach (TLIF+ALIF)) divided into 2 groups: general anesthesia (GA, n=24) and general anesthesia combined with ESPB (GA+ESPB, n=21). Primary outcome was to analyze the efficacy of ESPB in two different surgical approaches in terms of pain intensity in the first 48 hours. Secondary -Fentanyl free patients and opioid consumption in the first 24 hours postoperatively. Comparative analysis was performed (SPSS® v. 28.0). P<0.05.Out of 45 patients (27 female), 21 received GA+ESPB and 24 received GA. Average age was 60.3±14.3 years. Chronic back pain before the operation was registered in 56% of patients. ESPB was performed in 17 TLIF and in 4 TLIF+ALIF patients. ESPB significantly reduced pain intensity at rest in both surgical approaches 48 hours after surgery; p<0.05. The need for postoperative fentanyl infusion was significantly lower in the group treated with GA+ESPB in both surgical approaches, that those who only received GA (29% vs 77% in TLIF and 0% vs 80% in TLIF+ALIF); p=0.01 un p=0.004. Additionally, we observed that ESPB provides a good analgesic affect for up to 6.8±3.2 h in the TLIF and 8.9±7.6 h in the TLIF+ALIF approaches. Consequently, ESPB reduced the initiation of the Fentanyl compared to GA alone, with a mean difference 3.2±4.2 h in TLIF subgroup (p=0.045) and 6.7±5.3 h in TLIF+ALIF (p=0.028). Only in TLIF+ALIF approach, ESPB reduced total Fentanyl consumption compared to those with GA 1.43±0.45 mg/24h vs. 0.93±0.68 mg/24h; p=0.015. Conclusions: ESPB significantly reduced pain at rest after surgery, the number of patients requiring immediate postoperative Fentanyl analgesia and total Fentanyl consumption in both surgical This is a provisional file, not the final typeset article approaches, particulary in TLIF+ALIF. However, application of ESPB doesn't always provide completely sufficient analgesia.